2019
DOI: 10.1002/pbc.27896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sirolimus on coagulopathy of slow‐flow vascular malformations

Abstract: Background/Objectives: Stagnant blood flow present in slow-flow vascular malformations can lead to localized intravascular coagulopathy (LIC), measured by elevated D-dimer levels, low fibrinogen, and/or thrombocytopenia. LIC can lead to localized thrombosis and/or bleeding, resulting in pain, swelling, and functional limitations. Patients with complex vascular malformations treated with sirolimus show clinical improvement in these symptoms. We hypothesized that the clinical benefits of sirolimus may correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 15 publications
(49 reference statements)
3
41
0
Order By: Relevance
“…A previous study that included 15 patients on sirolimus with slowflow vascular malformations demonstrated a significant decrease in D-dimer, suggesting that sirolimus therapy could improve the coagulopathy often seen in their disease. 20 Although we had no patient with severe LIC (definition <150 fibrinogen and D-dimer >2) in this current study, four patients were on sirolimus during the time of the procedures. This may have prevented these patients having significant changes in TEG parameters and/or bleeding/clotting complications.…”
Section: Resultsmentioning
confidence: 81%
“…A previous study that included 15 patients on sirolimus with slowflow vascular malformations demonstrated a significant decrease in D-dimer, suggesting that sirolimus therapy could improve the coagulopathy often seen in their disease. 20 Although we had no patient with severe LIC (definition <150 fibrinogen and D-dimer >2) in this current study, four patients were on sirolimus during the time of the procedures. This may have prevented these patients having significant changes in TEG parameters and/or bleeding/clotting complications.…”
Section: Resultsmentioning
confidence: 81%
“…Two patients also had normalization of fibrinogen on treatment. Thirteen patients (87%) self‐reported clinical improvement, primarily with reduction of pain and swelling within one to three months of starting sirolimus 23 . Although these results are encouraging, further studies are needed to determine if targeted therapies such as sirolimus not only improve coagulation laboratory abnormalities but also short‐ and long‐term hematologic complications in individuals with SFVM.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological management is often the first line option to achieve hemostatic stability in KMP. According to the literature, the response time of Sirolimus is 1 day to 4 weeks for KHE and 1-3 months for vascular malformations [7] [13] [18] [19]. KHE or VMs are the main lesions that cause coagulopathy and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%